Vital signs : perspectives on the health of American campaigning - Dulio, David A. (Brookings Institution Press, 2005)
"Through analysis of the 2004 presidential campaigns of George W. Bush and John F. Kerry, explores the strengths and weaknesses of the current U.S. campaign system and possible approaches to improving campaign conduct"--Provided by publisher